Separation of Goniocotes Burmeister, 1838, and Dictyocotes Kéler, 1940 (Phthiraptera: Ischnocera), with descriptions of four new species - Gustafsson, Daniel R.; Tian, Chunpo; Ren, Mengjiao; Li, Zhu; Sun, Xiuling; Zou, Fasheng (European Journal of Taxonomy, 2024)
The ischnoceran louse genus Dictyocotes Kéler, 1940, has long been considered a synonym of Goniocotes Burmeister, 1838, but the genus has never been revised. Here, the relationships within and between Goniocotes and Dictyocotes are discussed, and the latter genus is resurrected from synonymy. Both genera are redescribed, and four new species of lice are described and illustrated. They are: Dictyocotes furcatus sp. nov. ex Lophophorus lhuysii Geoffroy Saint-Hilaire, 1866; Goniocotes cacumentalis sp. nov. ex Tetraogallus tibetanus Gould, 1854; Goniocotes caoi sp. nov. ex Chrysolophus pictus (Linnaeus, 1758); Goniocotes sarissa sp. nov. ex Tragopan caboti (Gould, 1857). The altitudinal distribution of these two genera is discussed, and appears to indicate a division between a primarily low-altitude Goniocotes and an exclusively high-altitude Dictyocotes. The driving force behind this division is unknown, but unlikely to be based on host associations.